“What happens next is up to you": encouraging Americans’ engagement in and communication about the issue of climate change - Gallivan, Nicholas P. (Kansas State University, 2023)
The purpose of these studies was to examine persuasive methods of climate change (CC) advocacy among Americans who feel strongly about this issue. Specifically, using the Global Warming’s Six Americas (Maibach, et al., 2011) framework, Alarmed and Concerned Americans were recruited to examine different appeals encouraging pro-environmental behaviors that varied by the number of proposed behaviors (seven versus one) and by the proposed actor of these behaviors (the participant themself versus legislators in the U.S. government; Study 1) and to establish the perceived efficacy of tools created to help individuals overcome behavioral barriers to CC opinion leadership (i.e., “Strategies” for initiating conversations about CC, “Counterarguments” to common misinformation and denial claims, and “Posts” that can be easily shared across social media sites; Study 2). In Study 1, participants were randomized to view one of four messages (Single Quantity–Self Actor, Single–Legislator, Multiple–Self, Multiple–Legislator) and completed a battery of attitudinal and behavioral measures related to CC. Against expectation, participants who read either of the two messages highlighting Multiple behaviors and either of the two messages highlighting Self-initiation were the more likely to engage, generally, in future pro-environmental behaviors; furthermore, participants who read the Multiple–Self message were more likely to engage in clean electricity practices and products. In Study 2, participants read four messages encouraging engagement in CC opinion leadership, with three of the messages including additional information to help overcome barriers to initiating difficult conversations. They also completed a personality assessment, which helped determine if participants’ effectiveness ratings of the messages uniquely corresponded with specific aspects of their personality. As projected, Agreeableness was positively related to the effectiveness ratings of the Posts message; additionally, Agreeableness was positively related to the effectiveness ratings of the Strategies message. However, lower Extraversion and higher Neuroticism were not uniquely related to effectiveness ratings for either of the three interventions as hypothesized. Clarification of these results, limitations of the study's methodology, and future research possibilities are also discussed.
Keywords: Climate change; Attitudes; Pro-environmental behaviors; Persuasion; Opinion leadership; Global warming's six Americas